Metabolic imaging of acute and chronic infarction in the perfused rat heart using hyperpolarised [1-13C]pyruvate - Ball, DR; Cruickshank, R; Carr, C; Stuckey, D; Lee, P; Clarke, K; Tyler, D (2013)
Hyperpolarised 13C MRI can be used to generate metabolic images of the heart in vivo. However, there have been no similar studies performed in the isolated perfused heart. Therefore, the aim of this study was to develop a method for the creation of 13C metabolite maps of the perfused rat heart and to demonstrate the technique in a study of acute and chronic myocardial infarction. Male Wistar rat hearts were isolated, perfused and imaged before and after occlusion of the left anterior descending (LAD) coronary artery, creating an acute infarct group. In addition, a chronic infarct group was generated from hearts which had their LAD coronary artery occluded in vivo. Four weeks later, hearts were excised, perfused and imaged to generate metabolic maps of infused pyruvate and its metabolites lactate and bicarbonate. Myocardial perfusion and energetics were assessed by first-pass perfusion imaging and 31P MRS, respectively. In both acute and chronically infarcted hearts, perfusion was reduced to the infarct region, as revealed by reduced gadolinium influx and lower signal intensity in the hyperpolarised pyruvate images. In the acute infarct region, there were significant alterations in the lactate (increased) and bicarbonate (decreased) signal ratios. In the chronically infarcted region, there was a significant reduction in both bicarbonate and lactate signals. 31P-derived energetics revealed a significant decrease between control and chronic infarcted hearts. Significant decreases in contractile function between control and both acute and chronic infracted hearts were also seen. In conclusion, we have demonstrated that hyperpolarised pyruvate can detect reduced perfusion in the rat heart following both acute and chronic infarction. Changes in lactate and bicarbonate ratios indicate increased anaerobic metabolism in the acute infarct, which is not observed in the chronic infarct. Thus, this study has successfully demonstrated a novel imaging approach to assess altered metabolism in the isolated perfused rat heart. © 2013 The Authors. NMR in Biomedicine published by John Wiley and Sons, Ltd.